Long-baseline neutrino facility (LBNF) and deep underground neutrino experiment (DUNE) conceptual design report volume 2: The physics program for DUNE at LBNF - Collaboration, DUNE; Acciarri, R; Acero, M; Adamowski, M; Adams, C; Adamson, P; Adhikari, S; Ahmad, Z; Albright, C; Alion, T; Amador, E; Anderson, J; et al. (Deep Underground Neutrino Experiment, 2015)
The Physics Program for the Deep Underground Neutrino Experiment (DUNE) at the Fermilab Long-Baseline Neutrino Facility (LBNF) is described.